Converging evidence does not support GIT1 as an ADHD risk gene. Issue 6 (10th June 2015) - Klein, Marieke; van der Voet, Monique; Harich, Benjamin; van Hulzen, Kimm J. E.; Onnink, A. Marten H.; Hoogman, Martine; Guadalupe, Tulio; Zwiers, Marcel; Groothuismink, Johanne M.; Verberkt, Alicia; Nijhof, Bonnie; Castells‐Nobau, Anna; et al.
Abstract : Attention‐Deficit/Hyperactivity Disorder (ADHD) is a common neuropsychiatric disorder with a complex genetic background. The G protein‐coupled receptor kinase interacting ArfGAP 1 ( GIT1 ) gene was previously associated with ADHD. We aimed at replicating the association of GIT1 with ADHD and investigated its role in cognitive and brain phenotypes. Gene‐wide and single variant association analyses for GIT1 were performed for three cohorts: (1) the ADHD meta‐analysis data set of the Psychiatric Genomics Consortium (PGC, N = 19, 210), (2) the Dutch cohort of the International Multicentre persistent ADHD CollaboraTion (IMpACT‐NL, N = 225), and (3) the Brain Imaging Genetics cohort (BIG, N = 1, 300). Furthermore, functionality of the rs550818 variant as an expression quantitative trait locus (eQTL) for GIT1 was assessed in human blood samples. By using Drosophila melanogaster as a biological model system, we manipulated Git expression according to the outcome of the expression result and studied the effect of Git knockdown on neuronal morphology and locomotor activity. Association of rs550818 with ADHD was not confirmed, nor did a combination of variants in GIT1 show association with ADHD or any related measures in either of the investigated cohorts. However, the rs550818 risk‐genotype did reduce GIT1 expression level. Git knockdown in Drosophila caused abnormal synapse and dendrite morphology, but did not affect locomotor activity. In summary, we could not confirm GIT1 as an ADHD candidate gene, while rs550818 was found to be an eQTL for GIT1 . Despite GIT1's regulation of neuronal morphology, alterations in gene expression do not appear to have ADHD‐related behavioral consequences. © 2015 Wiley Periodicals, Inc.